2023
DOI: 10.3390/ma16031005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Long-Term Performance of an Existing Warm Recycled Motorway Pavement

Abstract: Warm mix asphalt (WMA) technologies allow the production, lay-down and compaction of asphalt mixtures at reduced temperatures and the use of higher amounts of reclaimed asphalt pavement (RAP) with respect to conventional hot mix asphalt (HMA), leading to significant environmental benefits and energy savings. However, limited data is available on the long-term performance of such pavements. The objective of this study was to predict the long-term performance of an existing warm recycled motorway pavement (made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Materials 2023, 16,5686 results in a reduction in asphalt content, which yet impairs the flexibility of binder.…”
Section: Pup and Chain Extender Content Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials 2023, 16,5686 results in a reduction in asphalt content, which yet impairs the flexibility of binder.…”
Section: Pup and Chain Extender Content Determinationmentioning
confidence: 99%
“…The WMA technology may have a detrimental influence on the rutting resistance of the mixture, which can be alleviated by increasing RAP content and adding rejuvenators [ 15 ]. Lorenzo I. et al [ 16 ] predicted the long-term performance of an existing warm recycled highway pavement in Italy on the basis of the simplified viscoelastic continuum damage (S-VECD) testing approach. The results demonstrated that the WMA pavement possesses longer service life than the HMA pavement.…”
Section: Introductionmentioning
confidence: 99%